The Effect of Consuming Boiled Eggs on the Acceleration of Healing of Post Sectio Caesarea Wounds in the Working Area of the Pandanwangi Health Center, Malang City - Subekti, Imam (Al-Hijrah Indonesia, 2024)
Caesarean Section (CS) is a surgical procedure to give birth to a baby by making an incision in the uterine wall. Healing of CS wounds requires high protein, but many mothers avoid protein-rich foods for fear of worsening the wound. One of the nutrients that is high in protein, economical, and easy to find is eggs, because one egg contains > 90% Ca and Fe, 9 essential amino acids, and 6 grams of quality protein proven to accelerate wound healing. The purpose of this study was to determine the effect of boiled eggs on accelerating wound healing Post Sectio Caesarea in the work area of the Pandanwangi Health Center, Malang City in 2024. This research method uses a Quasi Experiment design, the sampling method uses a purposive sampling technique with a sample size of 22 people divided into treatment groups and control groups. Data analysis used is univariate analysis and bivariate analysis with the Chi Square test. The results of the study obtained 11 Post Sectio Caesarea mothers who consumed boiled chicken eggs, 9 (81.8%) experienced faster healing compared to the control group (27.3%). Consumption of boiled chicken eggs showed a significant effect on the healing time of stitches in mothers after post-Cesarean section (p-value = 0.030). It is expected that health center officers can provide education to post-Cesarean mothers about the benefits of boiled eggs in accelerating the healing of Cesarean wounds.